Identificação de forças de excitação em sistemas rotativos utilizando funções ortogonais - Oliveira, Marcos Vinicius Alves de [UNESP] (2013)
Rotating machines are composed by several components which acts together causing a variety of phenomena. Undesirable phenomena as unexpected stops and failures can produce damage, this facts make engineers worry about the development of new techniques on structural health monitoring (SHM) of the whole set of components. In order to avoid severe damage, a constant monitoring of machines is usually employed. One of the new approaches on (SHM) is the identification of parameters and excitation forces. With the knowledge of the excitation forces in a rotating machine, it is possible to estimate the effort alterations caused by lack of lubrication, wear and geometrical variations in the system. In this dissertation the Fourier series and Legendre polynomials identification of parameters methods, based on orthogonal functions are used in rotating systems. These systems are discretized in beam elements in which each node have four degree of freedom: two displacements and two rotations. Force identification from this kind of orthogonal functions begins with the construction of an operational matrix for the integration of vectors from orthogonal bases, which enables a conversion of the set of key differential equations of the system by a set of algebraic equations; and then the to obtain the unknown excitation forces